Pengaruh Interpersonal Relationship Terhadap Problematic Internet Use pada Remaja Di Sumatera Barat - Arista, Lisa (Indonesian Journal of Innovation in Education Research, 2025)
This study aims to examine the influence of interpersonal relationships on problematic internet use among adolescents in West Sumatra. Adolescents are an age group in a stage of social development that is vulnerable to various environmental influences, making interpersonal relationships an important factor in their daily lives. This study employed a quantitative approach using simple linear regression analysis to test the proposed hypothesis. The analysis results showed a significant influence of interpersonal relationships on problematic internet use, with a significance value of 0.000 (< 0.05) and a regression coefficient of -0.124. These findings indicate that the higher the quality of adolescents' interpersonal relationships, the lower their tendency to experience problematic internet use. However, the R Square value of 0.035 suggests that interpersonal relationships contribute only 3.5% to the tendency of problematic internet use, while the remaining 96.5% is influenced by other factors not examined in this study. These findings highlight the importance of strengthening interpersonal relationships as an effort to prevent problematic internet use among adolescents.